2002
DOI: 10.1126/science.1066901
|View full text |Cite
|
Sign up to set email alerts
|

Adult-Onset Primary Open-Angle Glaucoma Caused by Mutations in Optineurin

Abstract: Primary open-angle glaucoma (POAG) affects 33 million individuals worldwide and is a leading cause of blindness. In a study of 54 families with autosomal dominantly inherited adult-onset POAG, we identified the causative gene on chromosome 10p14 and designated it OPTN (for "optineurin"). Sequence alterations in OPTN were found in 16.7% of families with hereditary POAG, including individuals with normal intraocular pressure. The OPTN gene codes for a conserved 66-kilodalton protein of unknown function that has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
795
11
12

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 924 publications
(857 citation statements)
references
References 16 publications
14
795
11
12
Order By: Relevance
“…Second, Rab8 interacts with FIP-2 (optineurin) that also modulates cell morphogenesis and links Rab8 to the huntingtin protein (Li et al, 1998;Hattula and Peränen, 2000). Interestingly, mutations in optineurin cause primary open-angle glaucoma (Rezaie et al, 2002). In ADPKD (autosomal dominant polycystic kidney disease) cells loss of polarity is associated with redistribution of Rab8, suggesting a role of Rab8 in controling epithelial polarity (Charron et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Second, Rab8 interacts with FIP-2 (optineurin) that also modulates cell morphogenesis and links Rab8 to the huntingtin protein (Li et al, 1998;Hattula and Peränen, 2000). Interestingly, mutations in optineurin cause primary open-angle glaucoma (Rezaie et al, 2002). In ADPKD (autosomal dominant polycystic kidney disease) cells loss of polarity is associated with redistribution of Rab8, suggesting a role of Rab8 in controling epithelial polarity (Charron et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, these loci and genes may account for only a small proportion of glaucoma seen in the general population. Studies of MYOC and OPTN mutations in the general glaucoma population have shown that they account for 3.4% of open angle glaucoma 65 and up to 15% of NTG, 64 respectively. The association of two intronic OPA1 polymorphisms in the OPA1 gene with normal tension glaucoma (IVS8 þ 4C/T and IVS8 þ 32T/C), 66,67 is of interest since NTG may account for 20-50% of open angle glaucoma.…”
Section: Glaucomamentioning
confidence: 99%
“…11,12 In 1987, Teikari estimated the heritability of chronic open-angle glaucoma to be 13%, based on the Finnish Twin Cohort Study, 13 which supports a polygenic and/or multifactorial mode of transmission. To date, 6 different chromosomal loci have been identified for POAG, 14 -19 including the myocilin (MYOC) 20 and optineurin (OPTN) 21 genes.…”
mentioning
confidence: 99%